1979
DOI: 10.1128/aem.37.4.693-696.1979
|View full text |Cite
|
Sign up to set email alerts
|

Production of 3-acetoxyscirpene-4,15-diol from anguidine (4,15-diacetoxyscirpene-3-ol) by Fusarium oxysporum f.sp. vasinfectum

Abstract: Growing cells of Fusarium oxysporum f.sp. vasinfectum (ATCC 7808) formed 3-acetoxyscirpene-4,15-diol from anguidine (4,15-diacetoxyscirpene-3-ol) by way of the intermediates triacetoxyscirpene, 3,4-diacetoxyscirpene-15-ol and 3,15-diacetoxyscirpene-4-ol. The new 3-acetoxy analog was found to be less active than anguidine and the two other monoacetoxy derivatives when tested against a series of fungal strains and against HeLa cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A number of in vitro studies on the metabolism of TCTC in animals have shown that hydroxylases and esterases in the liver play an important role in diverse structures and their toxicities [Ohta et al, 1977[Ohta et al, , 1978Swanson and Corley, 1989;Ueno et al, 1983;Wei and Chu, 1985;Yoshizawa and Morooka, 19751. Fungal esterases from crude extracts or with whole mycelia have also been shown capable of hydrolyzing TCTC [Baldwin et a]., 1986;Claridge andSchmitz, 1978, 1979;Kotsonis and Ellison, 1975;Udell and Dewick, 1989;Yoshizawa and Morooka, 19751. Whereas both intracellular and extracellular esterases have been found, intracellular esterases were found to be primarily involved in the hydrolytic reactions [Udell and Dewick, 1989;Ueno et al, 1973;Yoshizawa and Morooka, 19751.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of in vitro studies on the metabolism of TCTC in animals have shown that hydroxylases and esterases in the liver play an important role in diverse structures and their toxicities [Ohta et al, 1977[Ohta et al, , 1978Swanson and Corley, 1989;Ueno et al, 1983;Wei and Chu, 1985;Yoshizawa and Morooka, 19751. Fungal esterases from crude extracts or with whole mycelia have also been shown capable of hydrolyzing TCTC [Baldwin et a]., 1986;Claridge andSchmitz, 1978, 1979;Kotsonis and Ellison, 1975;Udell and Dewick, 1989;Yoshizawa and Morooka, 19751. Whereas both intracellular and extracellular esterases have been found, intracellular esterases were found to be primarily involved in the hydrolytic reactions [Udell and Dewick, 1989;Ueno et al, 1973;Yoshizawa and Morooka, 19751.…”
Section: Discussionmentioning
confidence: 99%
“…These toxicological effects are correlated with their chemical characteristics. Type A TCTCs possess hydroxyls or esterified hydroxyls at the C-3,4,7,8, or 15 positions; hydrolysis of the ester side chain generally results in a decrease of toxicity in experimental animals [Claridge andSchmitz, 1978,1979;Ueno, 1983;Yoshizawa and Morooka, 1975;Yoshizawa et al, 1980aYoshizawa et al, , 1980bYoshizawa et al, . 1982Swanson and Corley, 19891. Whereas metabolic hydrolysis of the ester bond of TCTCs by mammalian enzymes plays an important role in determining the toxicity of the toxin, the multiplicity of TCTCs produced by various fusaria was also attributed to the hydroxylase and esterase enzymes [Anonymous, 1983;Baldwin et al, 1986;Beeton and Bull, 1989;Desjardins et al, C 1996WileyLiss, Inc 1993Miller and Trenholm, 1994;Swanson and Corley, 1989;Udell and Dewick, 1989;Ueno, 19831.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological 3α-O-acetylation of trichothecenes, diacetoxyscirpenol and 15-acetoxyscirpene-3,4-diol by trichothecene nonproducing fungi of Mucor mucedo and F. oxysporum f. sp. vasinfectum was reported 98,99) .…”
Section: Acetyl Conjugation Of Trichothecenes 97)mentioning
confidence: 99%
“…We first found the microbial acetylation of trichothecenes in deoxynivalenol with resting mycelia of F. nivale, and the reaction occurred at C-3a position (12). Thereafter, Claridge and Schmitz (1,2) reported the biological 3a-O-acetylation of diacetoxyscirpenol and 15-acetoxyscirpene-3,4-diol by resting cells on Mucor mucedo and growing cells of F. oxysporum f. sp. vasinfectum.…”
Section: Discussionmentioning
confidence: 99%